Correcting Ryle’s Mistake: Motor Redundancy and the Embodied Intelligence of Habits - Jeferson Diello Huffermann (Principia: An International Journal of Epistemology)
Embodied cognition and enactive approaches have criticized the associationist, also called mechanistic, view of habits. Motivated by the enactive account of habits and research on the field of Motor Control, I argue that Ryle was both wrong and right about habits and their relation to intelligent behavior. Ryle was wrong in claiming that habits fall short of intelligent behavior. But Ryle was also right, he correctly puts habits in a continuity that goes from dispositions in general to what he considers bonafide intelligent behavior or knowing-how. After some background, the Rylean distinction between habits and intelligent behavior is explored. I then move to Ryle’s mistake and its roots, tacitly endorsing the idea of instinct as innate behavior. In doing so, he neglected that variability and modifiability are the rules and not the exceptions in behavior. Research on the phenomena of motor redundancy of animal behavior, the enactive account of habits, and a dynamic account of intelligence are mobilized to correct his mistake. My proposed account explains Ryle’s mistake, why it is a mistake, and why it is an understandable mistake coming from someone with his perspective. The last section of the paper re-articulates the continuum between simple dispositions, habits, and highly skilled behavior. I reconceived the continuum of intelligence as including not only our habits, but all animal behavior.